Purification of 3-indolylacetic acid by solid phase extraction - Rolcík, Jakub; Recinská, Jana; Bartak, Petr; Strnad, Miroslav; Prinsen, Els (Journal of separation science, 2005)
This paper deals with the use of solid-phase extraction (SPE) for the extraction and purification of 3-indolylacetic acid (IAA), the main and most important representative of the plant growth regulators auxins. The procedure is based on the use of C18-SPE columns in two steps. In the first one, raw extract in methanol:water (4:1) is applied on the column in order to remove neutral ballast. In the second step the eluate is diluted with water to a final methanol concentration of 20% (to decrease the elution strength of the solvent) and acidified with formic acid to a final concentration of 1% (to convert the IAA from the anionic to the neutral form). Neutral IAA is then retained on the second SPE column, eluted by (acidified) methanol, and subjected to final analysis. Scintillation counting of tritium labeled IAA standard was used for the investigation and optimization of the SPE procedure. Gas chromatography with mass spectrometric detection was suggested as a convenient method for routine determination of IAA after its methylation with diazomethane. Overall recovery of the procedure was estimated as 89-94% and a physiological level of IAA equal to 0.48 nmol/g (84 ng/g) fresh weight was found using an optimized SPE-GC-MS method.
Keywords: kyseliny indoloctové; Plant Growth Regulators; Plant Leaves; Chromatography, Liquid; Indoleacetic Acids; Pelargonium; regulátory růstu rostlin; plynová chromatografie s hmotnostně spektrometrickou detekcí; chromatografie kapalinová; Gas Chromatography-Mass Spectrometry; listy rostlin